The Feeling of Being Left Behind in The Middle of the Digital Era: Fomo and Life Satisfaction in Early Adulthood - Fariha Aulia Syahda; Dewi Handayani Harahap (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Fomo is an anxiety that cannot be separated from the virtual world, this phenomenon is often found on various social media platforms. The FoMO phenomenon experienced by individuals can affect the level of satisfaction they have, such as satisfaction with psychological needs, mood, and overall life satisfaction, along with their level of involvement in social media. the purpose of this study is to examine the relationship between Life Satisfaction and Fear of Missing Out (FoMO) in Early Adult Social Media Users in Seturan, Condongcatur, Depok, Babarsari (SCBD) Jogjakarta. This study uses quantitative research methods. The sampling technique used was purposive sampling. The results showed a Pearson correlation value of 0.528 with sig.0.000 (p0.05). This means that there is a significant influence between life satisfaction and the level of FoMO in early adulthood. Based on the results of data analysis in this study, a correlation of (r) 0.528 was obtained with a significance level of 0.000 (p ≤ 0.005) which indicates that there is a significant positive relationship between life satisfaction and FoMO in early adult social media users in the Seturan, Condongcatur, Babarsari, Depok area. Based on the Measure Associattion analysis, the r2 value is 0.278 or 27.8%, which means that there is an influence of life satisfaction on FoMO.Fear of Missing out (FoMO) merupakan suatu kecemasan yang tidak bisa lepas dari dunia maya, fenomena ini sering ditemukan berbagai platform media sosial. Fenomena FoMO yang dialami individu dapat mempengaruhi tingkat kepuasan yang dimiliki, seperti kepuasan terhadap kebutuhan psikologis, suasana hati, serta kepuasan hidup secara keseluruhan, seiring dengan tingkat keterlibatan mereka dalam media sosial. tujuan penelitian ini yaitu untuk menguji hubungan antara Kepuasan Hidup dengan FoMO pada Dewasa Awal Pengguna Sosial Media di Seturan, Condongcatur, Depok, Babarsari (SCBD) Jogjakarta. Penelitian ini menggunakan metode penelitian kuantitatif. Teknik pengambilan sampel yang digunakan adalah purposive sampling. Jumlah partisipan sebanyak 106 responden. Hasil penelitian menunjukkan nilai korelasi pearson sebesar 0,528 dengan sig.0,000 (p0,05). Artinya terdapat pengaruh yang signifikan antara kepuasan hidup dengan tingkat FoMO pada dewasa awal. Berdasarkan hasil analisis data pada penelitian ini, maka diperoleh korelasi sebesar (r) 0,528 dengan taraf signifikan 0,000 (p ≤ 0,005) yang menunjukkan bahwa terdapat hubungan positif yang signifikan antara kepuasan hidup dengan FoMO pada dewasa awal pengguna media sosial di daerah Seturan, Condongcatur, Babarsari, Depok. Berdasarkan analisis Measure Associattion bahwa nilai r2 0,278 atau 27,8% yang artinya terdapat pengaruh kepuasan hidup terhadap FoMO.